Embarking on a journey: a bibliometric analysis of the relative age effect in sport science - Bilgic, M.; Isin, A. (German Journal of Exercise and Sport Research, 2023)
The early identification and development of talented athletes has become increasingly popular in youth sport. However, such approaches may lead to undesired, biased practices. One such selection bias is relative age effect (RAE) which results in certain (dis)advantages for athletes based on their date of birth. Despite the growing interest in RAE in sports, no bibliometric analysis has been conducted to determine the publication trends. The purpose of this study was to provide a holistic view of research activity on RAE in sport sciences to identify publication trends, patterns, evolution of the field and progress over time. The analyses focused on the number of publications, document types, institutions, authors, journals, countries, continents and sports. Then, network visualization maps regarding keywords and authors were created. Our search yielded 281 publications which were predominantly from Europe (62.14%) followed by North America (22.19%), while Canada was the most productive country with 19.22% of all publications. Moreover, research mostly focused on soccer followed by ice hockey and basketball. The most frequently used keywords were as follows: relative age effect, talent identification and talent development. An increasing trend regarding the number of studies on RAE was noted with the year 2018 reaching the peak. This study offers insight into publication trends, patterns, and hot spots on RAE research in sport. Furthermore, it will help researchers to identify research frontiers and overlooked concepts for further studies in RAE.